Bibliometric Analysis of Gender Equality in Islam Analisis Bibliometrik About Gender Equality in Islam - Suhartini Suhartini (Green Publisher Indonesia, 2023)
Background: Gender inequality perpetuates social injustice. When individuals do not have equal opportunities based on sex, this results in inequities in education, employment, access to health, and political participation. Purpose: This research aims to conduct a bibliometric analysis related to gender equality in Islam. Method: The method used is bibliometric, which involves collecting and analyzing data from relevant scientific publications from the Scopus database. This research found 133 relevant publication documents related to gender equality in Islam Results: The results of the examination of publication documents also found several other relevant topics, including gender, Islam, feminism, gender equality, religion, women's status, women's rights, gender relations, family law, social media, public opening, the Middle East, politics, women, and articles. These topics are still subject to development, depending on the interest of global researchers. Trends in the results of this research also help to study the development of gender equality studies and networks in Islam. This can also be a global reference in understanding changes in study perspectives that can influence attitudes to further research. This research is based on the results of examining published documents, which can be a reference for future research, especially on gender equality in Islam, both internally and nationally. Conclusion: The limitation of this study lies in data screening, which is only limited to specific years of publication (2017-2023). This also affects the number of documents analyzed, so further research is needed to explore a more significant number of documents. This may affect better analysis results in the future.